Perceived Occupational Stressors and the General Health of Critical Care Nurses During COVID-19 Pandemic - Suhair Hussni Al-Ghabeesh RN, MsN, PhD; Raid Mahmmud Al-Awayssa RN, MsN; Ahmad Hussien Rayan PhD; Enas A Assaf RN, MsN, PhD (SAGE Publishing, 2022)
Introduction The COVID-19 situation is placing nurses under great stress which may negatively influence their health. Objective The purpose of this study was to examine the association between occupational stress and general health of critical care nurses during COVID-19 pandemic. Methods A descriptive, cross-sectional design was used. A convenience sample of 150 Jordanian critical care nurses completed the study. Results Occupational stress was a significant predictor of nurses' general health. Female gender, young, living with elderly or persons having chronic diseases, and little nursing experience were associated with worse general health, while living with elderly or persons having chronic diseases were associated with more occupational stress. Conclusion Providing psychological support services for critical care nurses is required to reduce the impact of occupational stress on nurses' poor general health.